Impact of nutrition intervention on the nutritional status and cognitive function among children (6-12 years) – An Interventional Study from South India: Formulation & Evaluation of Methotrexate and Triherbal Loaded Topical Emulgels for Anti-Arthritic Activity - Sah, Chandan; Battu, Dr. Sowjanya; Prasad Yadav, Deepak; Das, Ajay Kumar; Vishwanath, B. A. (Asian Journal of Pharmaceutical Research and Development, 2024)
Aim: The aim of this study was to prepare Methotrexate and triherbal loaded topical emulgels for anti-arthritic activity. Methods: The above sources are subjected to soxhlation and aqueous and hydroalcoholic extracts of the above three will be prepared. The extracts will be prepared by proper maceration in suitable solvents in required proportions. The resultant extract will be converted into emulgel as follows: The gel portion of the emulgel will be made by dissolving carbopol-934 in cold water with constant stirring at a moderate speed until uniform mixture is obtained. The pH was then adjusted to 6–6.5 using triethanolamine (TEA). Tween 80 was dissolved in distilled water to prepare the aqueous phase of the emulsion while for the preparation of the oil phase of the emulsion; span 80 was dissolved in liquid paraffin. To preserve the emulsion, benzalkonium chloride was dissolved in water and the suitable amounts of extracts and methotrexate is dissolved in ethanol then both solutions are mixed with the aqueous phase. Both the aqueous and the oil phase were heated in a water bath at 70 °C separately. Then the oil phase was added drop wise to the aqueous phase with continuous stirring using homogenizer at speed of 3000 rpm for 10 min then cold to room temperature. At the end the gel and emulsion portions were mixed in 1:1 ratio with moderately stirring to prepare emulgel. The preparation is made viscous to be spreadable on the skin sufficiently without friction by trial-and-error way of mixing different proportions of gelling polymers. The formulation thus prepared is subjected to suitable characterization and evaluation studies and the optimized formulation is reported after obtaining results. Results: Drug-polymer compatibility studies (FT-IR and DSC) showed no incompatibility between the drug and polymer. In- vitro permeation studies though egg membrane showed good drug release in the range of 78.91 to 98.92% over a period of 2 hours. The best formulation was found to be F3 showing in-vitro drug release of 98.92%. The correlation and coefficient (R2) values obtained from the kinetic equation shows the drug release from all the formulation (F1-F9) follow zero order drug release mechanism. Conclusion: It can be concluded that Methotrexate and Triherbal loaded Topical emulgels could be a better formulation approach for Anti-arthritic activity.